Multidisciplinary care for children with cleft lip and palate and their families: Family-Centered Care - Mariana Martire Mori; Camila Moraes Garollo Piran; Alana Vitoria Escritori Cargnin; Geovanna Mazia Caetano; Ana Claudia Tofalini; Thamires Fernandes Cardoso da Silva Rodrigues; Maria de Fátima Garcia Lopes Merino; Marcela Demitto Furtado (Universidade Federal do Rio Grande do Sul, 2024)
ABSTRACT Objective: To understand the multidisciplinary care provided to children with cleft lip and palate and their families. Method: Descriptive, exploratory and qualitative study, based on the theoretical-philosophical framework of Family-Centered Care, conducted with professionals from the multidisciplinary team of an association supporting individuals with cleft lip and palate. The data were processed using the Iramuteq® software and systematized using Similarity Analysis. The study was approved by the Ethics Committee under opinion no. 4,095,950. Results: Twelve professionals participated, in which the guiding thread for the construction of the classes was the link between the words: Child, Family, Treatment and Difficulty and the alignment with the principles of the Family-Centered Care philosophy, resulting in the following classes: 1. Portrait of assistance from the multidisciplinary team in caring for children and their families (Assistance and Monitoring); 2. Challenges experienced by the team in caring for children and their families (Barriers); and 3. Exercising their (essential) role as a member of the multidisciplinary team (Impact). Conclusion: Professionals who care for children with cleft lip and palate and their families encounter barriers during care. However, they provide support to family members and work collaboratively, from the perspective of family-centered care involving participation, dignity, respect, and information sharing.